2019
DOI: 10.1177/0040517519832843
|View full text |Cite
|
Sign up to set email alerts
|

Circulating solution for the degumming and modification of hemp fiber by the laccase–2,2,6,6-tetramethylpiperidine-1-oxyl radical–hemicellulase system

Abstract: Hemp fiber, as a kind of renewable textile fiber, has evoked much interest due to its excellent properties in various fields. It has been investigated in just one step to finish the process of chemo-enzymatic degumming and modification of hemp fiber, which is done in acetic acidsodium acetate buffer solution containing laccase (6.0 g), hemicellulase (0.3 g) and 2,2,6,6-tetramethylpiperidine-1-oxyl radical (0.3 g) under a mild condition (pH 5, 50C). The degumming effects of different batches of raw hemp fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The main difference in infrared spectra was between 2000-650 cm -1(Yeping et al 2019b). Results showed that cellulose characteristic peaks of samples existed all samples, including cellulose OH in-plane deformation adsorption around 1335 cm -1 , O-H plane bending vibration adsorption around 1205 cm -1 , C-O-C telescopic vibration adsorption around 1160 cm-1, cellulose glucose ring CO ether bond stretching vibration adsorption around 1050 cm -1 , C=O telescopic vibration adsorption around 1030 cm -1(Liu et al 2019).…”
mentioning
confidence: 93%
“…The main difference in infrared spectra was between 2000-650 cm -1(Yeping et al 2019b). Results showed that cellulose characteristic peaks of samples existed all samples, including cellulose OH in-plane deformation adsorption around 1335 cm -1 , O-H plane bending vibration adsorption around 1205 cm -1 , C-O-C telescopic vibration adsorption around 1160 cm-1, cellulose glucose ring CO ether bond stretching vibration adsorption around 1050 cm -1 , C=O telescopic vibration adsorption around 1030 cm -1(Liu et al 2019).…”
mentioning
confidence: 93%
“…To further identify the changes in the chemical composition of hemp fiber prepared by various methods, infrared spectroscopy analysis was carried out to observe the distribution of the main chemical bonds in the hemp components, as shown in Figure 4. The main difference in infrared spectra was between 2000-650 cm -1 (Yeping et al 2019b). Results showed that cellulose characteristic peaks of samples existed all samples, including cellulose OH in-plane deformation adsorption around 1335 cm -1 , O-H plane bending vibration adsorption around 1205 cm -1 , C-O-C telescopic vibration adsorption around 1160 cm-1, cellulose glucose ring CO ether bond stretching vibration adsorption around 1050 cm -1 , C=O telescopic vibration adsorption around 1030 cm -1 (Liu et al 2019).…”
Section: Chemical Analysis (Ft-ir)mentioning
confidence: 94%